Should CAH in Females Be Classified as DSD? - González, Ricardo; Ludwikowski, Barbara M. (Frontiers in Pediatrics, 2016)
Great controversies and misunderstandings have developed around the relatively recently coined term disorders of sex development or DSD. In this article we question the wisdom of including XX individuals with congenital adrenal hyperplasia (CAH) in the DSD category and develop arguments against it based on the published literature on the subject. It is clear that females with CAH assigned the female gender before 24 months of age and properly managed retain the female gender identity regardless of the Prader grade. Females with CAH and low Prader grades have the potential for a normal sexual and reproductive life. Those with greater degrees of prenatal androgen exposure (Prader grades IV and V) raised as females also identify themselves as females but experience more male like behavior in childhood, have a greater rate of homosexuality and have greater difficulty with vaginal penetration and maintaining pregnancies. Improvement in surgical techniques, better endocrinological, psychological and surgical follow up may lessen these problems in the future. Given the fact that the term DSD includes many conditions with problematic gender identity and conflicts with the gender assigned at birth, it may be appropriate exclude females with CAH from the DSD classification.